Konsep Smart Goal Setting Pada Bisnis M-Prod Demi Meningkatkan Bisnis Songket di Kota Palembang - Fitria Marisya (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Palembang City has one type of industry that produces typical South Sumatran products, namely songket weaving with different characteristics from songket weaving in other provinces. Ogan Ilir Regency is a songket producing center that has been formed for quite a long time and the largest songket craftsman center in South Sumatra Province. This study aims to determine the economic empowerment strategy of songket craftsmen typical of Palembang City by the Department of Industry, Trade, Cooperatives and MSMEs of Palembang City. The subjects of the study were songket craftsmen, songket sellers and apparatus at the Department of Industry, Trade, Cooperatives and MSMEs of Palembang City. The results of this study show that the economic empowerment strategy of songket craftsmen typical of Palembang City by the Department of Industry, Trade, Cooperatives and MSMEs of Palembang City that can be used, namely intensive strategies with market penetration, market development, product development or integration with various existing opportunities. The MSME policy made has not been able to overcome various problems that occur in songket craftsmen.